PENINGKATAN REAKTIVITAS SORBEN KALSIUM HIDROKSIDA DAN TANAH DIATOME (DE) - Mariana Hasyim (Purifikasi, 2011)
Gas emission from solid waste incineration contains dangerous gases such as sulfur oxides, hydrochloric acid, carbon monoxide, and others. Acid gas removal technology can be done by using dry and wet processes. The dry process is more economical than the wet process. However, the dry process has low efficiency in gas removal and sorbent utilization. One way to overcome this problem is to use a sorbent which has high reactivity. The aim of this research was to increase the reactivity of calcium hydroxide sorbent by using diatomaceous earth as silica source. The reaction between sulfur dioxide with calcium hydroxide to form calcium silicate hydrates (CaO.SiO2.2H2O), which has high porosity and reactivity. The experiment was carried out in two work phases. The first was preparation of sorbent and sorbent reactivity test. The sorbent preparation was done in a batch reactor by reacting calcium hydroxide and DE together with 100 g of water at various ratios of calcium hydroxide /DE with a weight ratio of water phase/solids of 10. The sorbent reactivity test was performed by determining methylene blue absorption by the sorbent. The results showed that the solid density and the weight of solid sample increased after the reaction. The conversion reaction increased with the increasing reaction temperature, mixing rate, and reaction time. The conversion rate was constant after 20 minutes. The highest conversion rate was obtained at 65oC. The experimental results also showed that the reactivity of combined Ca(OH)2/DE sorbent was higher than that of Ca(OH)2 only.